2021
DOI: 10.1007/s10750-021-04578-x
|View full text |Cite
|
Sign up to set email alerts
|

The Ponto-Caspian parasite Plagioporus cf. skrjabini reaches the River Rhine system in Central Europe: higher infestation in the native than in the introduced Danubian form of the gastropod Theodoxus fluviatilis

Abstract: The introduction of non-indigenous organisms in new areas in the context of host-parasite interactions is still poorly understood. This study aimed at a parasitological and histopathological comparison of two phylogenetically distinct forms of the freshwater snail Theodoxus fluviatilis in the River Rhine system: the native Northern-European form, which showed a decline for unknown reasons and is nowadays extinct in the River Rhine, and the non-indigenous Danubian form, which was introduced via the Main–Danube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Furthermore, T. fluviatilis individuals of haplotype F31 were less infested by the trematode Plagioparus cf. skrjabini (also an invader from the Caspian region) than individuals of the native haplotype (Rothmeier et al 2021). The presence of both non-native parasites and non-native hosts (or hosts of non-native haplotypes) outside their natural range may have an effect on native biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, T. fluviatilis individuals of haplotype F31 were less infested by the trematode Plagioparus cf. skrjabini (also an invader from the Caspian region) than individuals of the native haplotype (Rothmeier et al 2021). The presence of both non-native parasites and non-native hosts (or hosts of non-native haplotypes) outside their natural range may have an effect on native biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…The ML analysis for phylogenetical reconstruction revealed that individuals of the invading haplotype F31 belong to the Danubian group with haplotypes F38 (originally found in Ukraine; Bunje 2005) and MT563453 (recorded as a newly arriving haplotype in the northern part of the Upper Rhine in 2018; Rothmeier et al 2021) (Fig. 2).…”
Section: Intraspecific Cryptic Invasionmentioning
confidence: 99%